Effects of the Long-term Care Insurance on Health Among Older Adults: A Panel Data From China - Xin Ye; Mingzheng Hu; Hugo Lin (Kerman University of Medical Sciences, 2023)
Background  China's long-term care insurance (LTCI) has been launched since 2016 to ensure that older disabled people obtain affordable care services. However, rigorous evaluations of the health effects of China's LTCI pilots have been limited. This paper aimed to examine the effects of LTCI on health among older adults aged 60 years and above.Methods  Drawing from panel data of the China Health and Retirement Longitudinal Study (CHARLS), we used a propensity score matching (PSM) and difference-in-difference (DID) approach to identify the health effects of the LTCI program and reduce the selection bias. Further, heterogeneity of the effects was examined by physical and intellectual function to evaluate whether the effects differed among subgroups of older population.Results  The implementation of LTCI significantly improved self-rated health (β = 0.15, P < .05) and cognitive function (β = 0.59, P < .01) for older adults. The results were robust when keeping only those living in pilot cities (β = 0.31, P < .05 for self-rated health status; β = 0.98, P < .001 for cognitive function) or non-pilot cities (β = 0.14, P < .05 for self-rated health status; β = 0.60, P < .01 for cognitive function) as the control group. The effects of LTCI were especially manifested in older adults with physical disability (β = 0.13, P < .01 for self-rated health; β = 0.76, P < .001 for cognitive function) or intellectual disability (β = 0.16, P < .01 for self-rated health).Conclusion  From a policy perspective, these findings suggested that LTCI in China could benefit the health outcomes of older adults, especially those with physical or cognitive disabilities. Policy-makers can target resources more effectively to improve health outcomes for the most vulnerable populations.